Does Gender Diversity Moderate the Nexus Between Board Characteristics and Earnings Management? - Tonoy Roy; Ervina Alfan (Asian Journal of Business and Accounting, 2022)
Manuscript type: Research paper Research aims: This study examines the effect of board characteristics on earnings management and the moderating effect of gender diversity over this nexus by investigating 393 Bursa Malaysia listed companies from 2014 to 2018. Design/Methodology/Approach: This study applies the performance-adjusted Jones model (Dechow et al., 1996) and the performance-matched Jones model (Kothari et al., 2005) to measure accrual-based earnings management. Research findings: Based on the results, the agency theory fails to illustrate that board characteristics (i.e., defined by the attributes of board independence, board size, and non-CEO duality) are effective in reducing earnings management. On the other hand, the results show that gender diversity in independent directorship and board membership apparently reduces the level of earnings management. However, this research finds no significant moderating effect of gender diversity on the relationship between CEO duality and earnings management. Theoretical contribution/Originality: This study adds to the literature by demonstrating that the application of agency theory does not have a significant impact on reducing earnings management in the Malaysian context. Applying gender socialisation theory, the findings of this study show successful moderation of gender diversity in terms of reducing the level of earnings management. Practitioner/Policy implication: The results on gender diversity are likely of interest to policymakers to come up with regulations related to ensuring an increasing presence of female directors in the boardrooms to increase the board gender diversity. Research limitation: This study examines only three board characteristics under corporate governance, and measures only accrual-based earnings management. Moreover, the sample is restricted to only non-financial listed companies.